Space Matters in Rachel Cusk’s Arlington Park - Armelle PAREY (E-REA)
The purpose of this article is to investigate Rachel Cusk’s use of space in Arlington Park as a means of depicting her female characters – and some aspects of the contemporary female condition in the Western world. Cusk’s use of space in relation to the literature of the past offers in this respect a fruitful perspective. My hypothesis is that with this emphasis on space Cusk may be modernist in her narrative style but she deliberately remains close to the Victorians in her choice of themes and treatment of women characters in relation to space in order to make a strong feminist statement, in the sense that her novel examines the experience of sexual difference and gendered space to denounce them as a source of discrimination.